2019
DOI: 10.1140/epjc/s10052-019-6833-1
|View full text |Cite
|
Sign up to set email alerts
|

Generalized tachyonic teleparallel cosmology

Abstract: In this paper we propose a new dark energy model in the teleparallel alternative of general relativity, by considering a generalized non-minimal coupling of a tachyonic scalar field with the teleparallel boundary term. Within the framework of teleparallel gravity, the boundary coupling term is associated with the divergence of the torsion vector. Considering the linear stability technique for various potentials and couplings, we have analyzed the dynamical properties of the present tachyonic dark energy model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…( 14) can be regarded as a "good vielbein". Similarly, in the FRW cosmological models the f (T, B) gravitational dynamics preserves the form of the usual Friedmann equations (two equations) [37][38][39][40][41][42]. The choice of vielbein is a rather important issue, as it fixes the number of degrees of freedom of the theory, as seen particularly in a gravitational wave analysis of f (T, B) gravity [50].…”
Section: Metric Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 14) can be regarded as a "good vielbein". Similarly, in the FRW cosmological models the f (T, B) gravitational dynamics preserves the form of the usual Friedmann equations (two equations) [37][38][39][40][41][42]. The choice of vielbein is a rather important issue, as it fixes the number of degrees of freedom of the theory, as seen particularly in a gravitational wave analysis of f (T, B) gravity [50].…”
Section: Metric Equationsmentioning
confidence: 99%
“…A new teleparallel gravity model is the f (T, B) gravity, where B is the boundary term [34][35][36], that has attracted a lot of attention due this model features have, as well as good agreement with observational data to describe the accelerated expansion of the universe [37,38], and their significant results in cosmological perturbations and thermodynamics, and dark energy, and gravitational waves [39][40][41][42][43][44][45]. Furthermore, the gravity f (T, B) was studied in a brane scenario, where it was possible to observe that the additional term B induces changes on the energy density causing a split in the brane, also changing the gravitational perturbations [46].…”
Section: Introductionmentioning
confidence: 99%
“…However, when in analogy to the curvature based f (R) and scalar-tensor gravity, one extends the teleparallel theory by e.g. introducing an arbitrary function arXiv:1905.03305v2 [gr-qc] 29 Jul 2019 of the torsion scalar, f (T) [21,22], or nonminimally coupled scalar field in the action [23,24], or generalizes the theory further [25][26][27][28][29][30][31], then the field equations start to differ from their curvature based counterparts, and consequently can offer new or modified solutions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [45,46], the authors found a Teleparallel theory containing non-minimally couplings between a scalar field and both the scalar torsion T and the boundary term B, finding that this theory contains the standard non-minimally coupled theories based on the curvature [47,48]. This was further generalised to quintom models [49], non-local models [50,51] and specific scalar tensor scenarios [52][53][54], finding again that Teleparallel theories are broader than standard modified theories. Recently, a Teleparallel Horndeski theory was derived which can be written as standard Horndeski plus a correction depending on torsion [55].…”
Section: Introductionmentioning
confidence: 92%

String-inspired Teleparallel Cosmology

Bahamonde,
Marciu,
Odintsov
et al. 2020
Preprint
Self Cite